Town Planning Schemes and Fortifications of the Map by R. d’Otto (1772) - Bevz, M.; Balahutrak, M. (Український історичний журнал, 2022)
The article examines the urban features, contained on the map of R. d’Otto since 1772. Novelty of the research. For Ukrainian scientists, the map is known only from the publication of its last sheet with the city of Lviv 2014. However, the map consists of 9 sheets and valuable information is also contained on the rest of its pages. The Otto’s map is a handwritten plan drawn up during the campaign of General Andreas Hadik’s army unit to Lviv when the region and city included to the Austrian state. The map is noteworthy because it is actually the first survey that captures in detail the topography and urban structure of our territories. Of particular value is d’Otto’s desire to fix the defensive objects that were in his view, to schematically outline the basic planning character of the city, fixing the main squares, temples, main buildings. Many of these objects are not extant or preserved in transformed form. The purpose of our work is to introduce these objects into scientific circulation and to analyze their planning structure, historical and urban value. The research methodology required the preparing of enlarged hand-drawn outlines of the towns and castles, since the images on the map themselves are drawn on a very small scale. Subsequently, we identified the nature of city planning schemes and objects, analyzed their value and condition. The conclusions show the uniqueness and historical value of the town planning schemes and fortifications. Materials can be useful for planning archaeological researches in cities of Skelivka (Felshtyn), Susidovychi, Rudky, Navaria, Lviv.